2020
DOI: 10.6007/ijarbss/v10-i9/7855
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Students’ Satisfaction and Intention to the Continuation of Online Distance Learning

Abstract: The COVID-19 pandemic has changed the educational landscape of Malaysia. The government's drastic action to implement the Movement Control Order (MCO) has forced all institutions of higher learning (IsHL) and schools to temporarily shut down. Learning activities had to continue, so online classes have been set up. Academicians and students have to adapt to the new learning environment. In Universiti Teknologi MARA (UiTM), Online Distance Learning (ODL) was implemented. The drastic change has become a challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
6
2
Order By: Relevance
“…Liaw and Huang [16] found that male college students tended to have more positive attitudes toward e-learning than female college students. In contrast, some research studies concluded that gender did not affect students' satisfaction with online learning [17][18][19]. Uniquely, the result of the current study showed that female university students were more satisfied with the online liberal arts courses than their male counterparts.…”
Section: Predictors Of Student Satisfaction With Online Liberal Arts Coursescontrasting
confidence: 84%
See 1 more Smart Citation
“…Liaw and Huang [16] found that male college students tended to have more positive attitudes toward e-learning than female college students. In contrast, some research studies concluded that gender did not affect students' satisfaction with online learning [17][18][19]. Uniquely, the result of the current study showed that female university students were more satisfied with the online liberal arts courses than their male counterparts.…”
Section: Predictors Of Student Satisfaction With Online Liberal Arts Coursescontrasting
confidence: 84%
“…Since 2020, the Coronavirus Disease-19 (COVID- 19) pandemic has made it difficult to offer traditional face-to-face courses to students in all types of academic institutions in South Korea. In response, most academic institutions have adopted distance education using information technology to develop online learning as the main mode of education delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the current study, other studies didn't show gender differences in online learning readiness (42)(43)(44)(45). Other studies reported that females were found to be more ready than males (30,46).…”
Section: Sociodemographic Factorscontrasting
confidence: 83%
“…The type of online learning tools and variations in the eld that the students are learning might be other reasons for the different ndings. In the current study, all students were the year I and learning medicine at which stress is high, while the students in the previous study were learning business and management in different study years (43). At the same time, while Cisco WebEx online learning tool was used in the current study, google meet and other online learning tools were used in the previous studies.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…In addition, Alghamdi et al, (2020) concluded that females had stronger self-regulation than males which contributed to better achievement of online learning outcomes. Gender was used as a control variable as similar international studies investigated it as a factor affecting academic success in online liberal courses during COVID-19 (Choi, 2021) and online distance learning (Mohamad, 2020).…”
Section: Control Variablesmentioning
confidence: 99%